Environmental Psychological Characteristic Supporting the Football Player’s Development in Indonesia and Malaysia - Akbar, Amin; Karim, Zulakbal Abd; Zakaria, Jaffry (Physical Education Theory and Methodology, 2024)
Background. The development path of a football player toward becoming a professional player involves four main aspects: physical, technical, tactical, and psychological ones. Objectives. This study aimed to examine the psychological characteristics of the environment that influence and contribute to the development of football players under 17 years old in Indonesia and Malaysia. Materials and methods. This study used a qualitative approach, namely evolved grounded theory, and the data collection process was conducted using three distinct methods: semi-structured interviews, observation, and document analysis. Twenty-five coaches participated in this study, comprising fifteen coaches from various football academies in Malaysia and ten coaches from Indonesia. All coaches involved in this study have a license and at least five years of experience as coaches under 17. The data collected and analyzed began with open coding, axial coding, and selective coding, and the analysis was assisted by using qualitative research software, namely N-Vivo 14. Results. The findings revealed that several aspects influenced player development, such as policy support, including structured and competitive age group competitions, a healthy football ecosystem; other results have been defined as relationships and cooperation supported by family, friendship between clubs, and teamwork. Finally, the study underscored the significance of involving coaching factors, including passion, patience, and coach psychological treatment abilities. These are the psychological characteristics of the environment that can influence the development of football players. Conclusions. It is hoped that the results of this study can be used as a reference for coaches, the Indonesian Football Association, and the Malaysian Football Association to create a policy that can support football players under 17 years from all aspects, including psychology.